Trends in Breast Cancer Staging at Diagnosis Associated with Screening Campaigns in Lebanon - Christiane J. El Khoury; Salim M. Adib; Monique Chaaya; Khalil El Asmar; Maya Charafeddine; Nagi S. El-Saghir (Mary Ann Liebert, 2020)
Introduction: Mammography screening has been shown to improve early breast cancer (BC) detection, by shifting the disease at diagnosis to locally confined stages, offering lighter treatments and better prognoses. BC awareness campaigns calling for annual mammography screenings have been ongoing in Lebanon since 2002. Changes in BC staging at diagnosis as a consequence of documented improvements in mammography uptake remain to be described. Materials and Methods: We reviewed 2,822 BC cases identified by pathology reports in the American University of Beirut Medical Center between the years 1990 and 2015. After age stratification, we have trended the extracted stages versus time. Results were compared between the prescreening (1990?2001) and the postscreening period (2002?2015). Results: During the postscreening period, stage I represented 31%, stage II 47%, stage III 14%, and stage IV 8% of the cases. Stage I cases had more than doubled whereas stage III cases showed a mirror decrease compared with the years before the implementation of awareness campaigns. The increase in stage I was significantly more prominent in women aged 40 years and older (from 14% to 32%), compared with the younger group. Shifts in staging happened in parallel with a concurrent rise in reported uptake of mammography screening. Conclusions: Our findings demonstrate significant trends in earlier detection, which are likely associated with an increase in screening uptake and an awareness of BC as a public health issue. Staging data from hospitals all over Lebanon should be available for building national evidence. The Ministry of Public Health should require reporting of BC stage at diagnosis to the National Cancer Registry, as part of the annual cancer incidence reporting in Lebanon.